186k views
0 votes
Multiply each equation by a constant that would help to eliminate the y terms. 2x-5y=-21 3x-3y=-18

User Bang
by
5.0k points

2 Answers

4 votes

Answer:

6x - 15y = -63

15x -15y = -90

User Jazzzzzz
by
5.5k points
4 votes


\left\{\begin{array}{ccc}2x-5y=-21&\text{multiply both sides by 3}\\3x-3y=-18&\text{multiply both sides by (-5)}\end{array}\right\\\\\underline{+\left\{\begin{array}{ccc}6x-15y=-63\\-15x+15y=90\end{array}\right}\qquad\text{add both sides of the equations}\\.\qquad-9x=27


\text{solution:}\\\\-9x=27\qquad\text{divide both sides by 9}\\x=-3\\\\\text{Substitute the value of x to the first equation:}\\\\2(-3)-5y=-21\\-6-5y=-21\qquad\text{add 6 to both sides}\\-5y=-15\qquad\text{divide both sides by (-5)}\\y=3\\\\\boxed{x=-3\ and\ y=3}

User Jaclynn
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.